PEMBELAJARAN AL-QUR’AN DI SINGKAWANG QUR’AN CENTER - Herwani Herwani (JURNAL PENDIDIKAN DAN KEGURUAN, 2023)
Singkawang Quran Center (SQC) serves and prepares human resources who have high competence in the field of the Qur'an, have noble character and have broad knowledge. The Singkawang Quran Center (SQC) is here for Muslims in Singkawang and its surroundings to improve the quality of their ability to read the Quran and memorize it and practice its teachings. Teaching the Qur'an properly and correctly according to the sanad is very necessary so that in pronunciation and daily practice there are no confusions that go down and down because it comes from a teacher whose ability to read the Qur'an is clear. Learning the Qur'an and teaching it is a noble job and is the best human being. In this case the programs that have been implemented include adult male and female tahsin, intensive tahfiz for children and adolescents, the Toddler Tahfiz Program (PROTABA) from 3 to 7 years of age. Al-Quran education at the Singkawang Quran Center (SQC) has experienced a significant development with the opening of a prayer stall around the Singkawang city bird park which is held every Sunday from six to eight in the morning. The participants consist of children, teenagers and parents for free This is done so that the people of Singkawang city really feel the presence of SQC full of wisdom and can share knowledge of the Koran with the people of Singkawang city and its surroundings. In the next two years, thank God the Singkawang Quran Center has developed Al Quran Education to a higher elementary school level. dominant in teaching the Koran to children. Singkawang Quran Center (SQC) has continued to develop, this is evidenced by the existence of Protaba (Tahfidz Toddler Program) which is dominant in teaching Al-Quran reading and memorization. In addition to the Protaba, there is an intensive tahfidz opening, which on average is a high school graduate and stays at Tahfidz's house with free fees. It has been more than two years since SDIT Ibnu Masud has been established at the Singkawang Quran Center (SQC) whose curriculum is more dominant in reading and writing the Koran and memorizing the Koran. The steps in memorizing the Qur'an as implemented at the Singkawang Qur'an Center (SQC) are sincerity, talaqqi and musyafahah, targeting memorization, choosing the time and place, determining the beginning of memorization,understanding, using one manuscript, diligently listening, and continuing to maintain ro.